1982
DOI: 10.1021/jm00349a006
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological activity of some very hydrophobic superagonist analogs of luteinizing hormone-releasing hormone

Abstract: The effect of increased hydrophobicity at position 6 of luteinizing hormone-releasing hormone (LH-RH) has been investigated by the incorporation of a series of 15 very hydrophobic, unnatural D-amino acids at this position. The unnatural amino acids studied can be considered analogues of phenylalanine with carbocyclic aromatic side chains consisting of substituted phenyl (e.g., 2,4,6-trimethylphenyl, p-biphenyl) or polycyclic aromatic (e.g., naphthalene, anthracene) units. When enzymatic resolution (subtilisin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
28
0
2

Year Published

1984
1984
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(30 citation statements)
references
References 17 publications
(21 reference statements)
0
28
0
2
Order By: Relevance
“…The effects of D-ureidoalkylamino acid residues on overall hydrophobicity or hydrophilicity of a peptide as compared to the related basic amino acids, such as D-Om7, D-Lys, and D-Arg, were estimated by HPLC. Compounds Al, their D-Orn6/D-Lys6 analogs, compounds A2, and the D-Arg6-containing antagonist II and its D-Nal(2) analog (VI) were analyzed by HPLC under isocratic conditions using 0.03 M ammonium acetate in 40% (vol/vol) aqueous acetonitrile as eluent at pH 7.2 (24,25). The capacity factor k' was used as a measure of the overall hydrophobicity of the analogs.…”
mentioning
confidence: 99%
“…The effects of D-ureidoalkylamino acid residues on overall hydrophobicity or hydrophilicity of a peptide as compared to the related basic amino acids, such as D-Om7, D-Lys, and D-Arg, were estimated by HPLC. Compounds Al, their D-Orn6/D-Lys6 analogs, compounds A2, and the D-Arg6-containing antagonist II and its D-Nal(2) analog (VI) were analyzed by HPLC under isocratic conditions using 0.03 M ammonium acetate in 40% (vol/vol) aqueous acetonitrile as eluent at pH 7.2 (24,25). The capacity factor k' was used as a measure of the overall hydrophobicity of the analogs.…”
mentioning
confidence: 99%
“…Our preliminary studies on the suppression of sexual function and reversibility in male dogs have been reported elsewhere (Vickery et ai, 1984a;Vickery & McRae, 1984). In the present study nafarelin acetate (Nestor et al, 1982) (Hoist & Phemister, 1975 In some studies 32 µg nafarelin were administered once daily by subcutaneous injection. The concentration of injection solution was 100 µg/ml and the injection volume was 0-32 ml.…”
Section: Introductionmentioning
confidence: 64%
“…Uterine palpation at 3-5 to 4 weeks after mating identified two implantation sites in Bitch C and none in Bitches A and B. (Nestor et al, 1982) and is, as are other analogues, being intensively evaluated as an ovulation inhibitor for women (Bergquist, Nillius & Wide, 1982 ;Nillius, Bergquist, Gudmundsson & Wide, 1984). …”
Section: Introductionmentioning
confidence: 99%
“…O hormônio de liberação do hormônio luteinizante (LHRH), por exemplo, pode ser liberado de maneira contínua para o tratamento do câncer de próstata e de maneira pulsátil para o tratamento da infertilidade. 43 Além disso, o controlador eletrônico pode ser ligado ou desligado quando necessário e, como o fármaco só é liberado na presença da corrente elétrica, o simples desligamento do controlador eletrônico provocará a diminuição do nível plasmático do fármaco. Esta característica permite a utilização da iontoforese na administração de opióides.…”
unclassified